Analisis Penerapan Corporate Social Responsibility (CSR) PT PLN Indonesia Power Up Indralaya dalam Meningkatkan Ekonomi Masyarakat di Desa Payakabung - Eva Susanti; Nia Andria Erzah; Meirina Alkhoiriah Eka Putri; Junaidi (Fakultas Ekonomi Universitas Tridinanti Palembang, 2025)
Abstract : This research discusses about analysis of the implementation of Corporate Social Responsibility (CSR) of PT PLN Indonesia Power UP Indralaya in improving the community economy in Payakabung Village. The aim of this research is to describe the implementation of Corporate Social Responsibility (CSR) of PT PLN Indonesia Power UP Indralaya in improving the economy of the community in Payakabung Village and knowing the impact of implementing CSR. The research method used in this research is qualitative research with the type of field research. The data collection techniques in this research are: (1) Observation, which aims to observe conditions in the field related to the implementation of CSR in improving the community's economy, (2) Interview, which aims to obtain in-depth information from several related informants, (3) Documentation Study, which the aim is to obtain data through existing documents in the form of archives related to CSR implementation related to company profile, history, vision and mission, organizational structure, CSR implementation reports related to research problems. Analysis of the data used through analysis activities before and after in the field. Data analysis before going to the field was carried out by studying literature reviews and secondary data. Data analysis in the field is carried out by data reduction, descriptive data presentation, verification and drawing conclusions. The research results show that the implementation of PT PLN Indonesia Power UP Indralaya's CSR has taken place from planning activities to the monitoring and evaluation stages of the CSR program. The research results also show that the implementation of CSR has had a positive impact on society which has led to economic improvements such as increasing people's income, providing employment opportunities, environmental management activities, and increasing people's knowledge and skills. Abstrak : Penelitian ini membahas tentang analisis penerapan Corporate Social Responsibility (CSR) PT PLN Indonesia Power UP Indralaya dalam meningkatan ekonomi masyarakat di Desa Payakabung. Adapun tujuan penelitian ini yaitu untuk mendeskripsikan terkait penerapan Corporate Social Responsibility (CSR) dan untuk mengetahui dampak dari penerapan CSR. Pengumpulan data pada penelitian ini adalah : (1) Observasi yaitu bertujuan untuk mengamati kondisi di lapangan terkait penerapan CSR dalam peningkatan ekonomi masyarakat, (2) Wawancara, yaitu bertujuan untuk memperoleh informasi mendalam dari beberapa informan yang terkait, (3) Studi Dokumentasi bertujuan untuk memperoleh data melalui dokumen yang telah ada dalam bentuk arsip terkait pelaksanaan CSR terkait profil perusahaan, Sejarah, visi misi, struktur organisasi, laporan implementasi CSR yang berhubungan dengan masalah penelitian. Analisis data yang digunakan melalui kegiatan analisis sebelum dan sesudah dilapangan. Analisis data sebelum dilapangan dilakukan dengan mempelajari kajian literatur dan data sekunder. Ananlisis data di lapangan dilakukan dengan reduksi data, penyajian data secara deskriptif, verifikasi, dan penarikan kesimpulan. Hasil penelitian menunjukan bahwa penerapan CSR PT PLN Indonesia Power UP Indralaya telah berlangsung dari kegiatan perencanaan hingga pada tahapan monitoring dan evaluasi program CSR. Hasil penelitian juga menunjukan bahwa penerapan CSR telah memberikan dampak positif bagi masyarakat yang mengarah pada peningkatan ekonomi seperti peningkatan pendapatan masyarakat, penyediaan lapangan pekerjaan, adanya kegiatan pengelolaan lingkungan serta peningkatan pengetahuan dan keterampilan masyarakat